The kids book of the night sky - Love, Ann (Kids Can Press, 2004)
Presents a guide to the night sky for young stargazers, offering advice on how to best view the night sky, and providing facts, legends, and activities associated with the moon, stars, and planets, as well as a look at seasonal attractions.